Methods of the Assessment of Economic Losses Caused by the Mortality of the Population Employed in Regional Economy - Kozlova, Olga Anatolyevna; Nifantova, Raisa Vikorovna; Makarova, Mariya Nikitichna (Economy of Regions, 2017)
The purpose of the study is to determine the most appropriate method to estimate the society losses from premature mortality. The authors compared the variants of the quantitative assessment of the economic losses caused by the mortality of the working-age population. The hypothesis of the research is the assumption that the researchers face the problem of choosing indicators for the analysis of various social and demographic groups of population, external factors and aims of calculation that can result in radically different results. On the grounds of domestic and foreign publications, the authors have analyzed preferable methodological tools to assess the economic losses and have defined the crucial factors affecting the estimated parameters. Using the example of the Sverdlovsk region and Ekaterinburg, we have evaluated the dynamics of the level and structure of working-age population mortality and estimated the economic losses from the mortality of working-age population for 2015 and 2016. The research uses two different methods to calculate the economic losses from the premature mortality of the working-age population. It has allowed to receive different evaluations of working people losses and to discuss the modification of socio-economic damage from the premature mortality taking into account regional characteristics. Thereby, we have defined gender and territorial differences of economic losses. Thus, the methodological tools allow estimating the economic losses of society caused by the premature mortality of working population both on the regional and municipal levels depending on the research purpose. The obtained results may be used to develop preventive measures for reducing mortality of the working population, increasing life expectancy and formulating the regional social policy.